The Role of Myth in Escalating The Conflict Between Israel-Palestine - Mujib, Abdul (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2019)
Myth as the basic of information before conducting life in society can escalate the sight toward other perspective, and make conflicting between Israel-Palestine. They are defending their myth. The myth of David and Goliath which stone as a tool in conquering the monster Goliath, it is been trying for youth Palestinian to beat Israel.Whereas, according to Abu Nimer, the reason for Palestinian using stone is like symbol that they want to show non-violent. However, by using stone, Israel fears that the story of David and Goliath will happen to them, yet the story is opposite. Now, the Israel becomes Goliath, and youth Palestinian becomes David who is throwing stone to the monster. By using Kepferer’s theory about power of myth, this article wants to analyze how strong the power of myth in the conflict of Israel-Palestine on the perspective of throwing stones.Keywords: Myth, Conflict, Israel, Palestine